Complete anatomy and figure drawing - Raynes, John. (London : Batsford, 2007)
Leading painter John Raynes' new book brings clarity to the anatomy of the human body in relation to the way we draw and paint it. An essential book for reference and inspiration, the book provides insight into drawing real people, not just the anatomically 'correct' shapes. All shapes and sizes are covered, from overweight and underweight to heavily pregnant. It shows how an understanding of anatomical form is vital to drawing all types of figures. John also encourages you to be more creative in your figure work.The comprehensive companion is illustrated with over 200 illustrations, many step-by-step.
Includes index.
Keywords: Anatomy, Artistic; Figure drawing